A coupled vegetation/sediment transport model for dryland environments. Issue 4 (12th April 2017) - Mayaud, Jerome R.; Bailey, Richard M.; Wiggs, Giles F. S.
Abstract: Dryland regions are characterized by patchy vegetation, erodible surfaces, and erosive aeolian processes. Understanding how these constituent factors interact and shape landscape evolution is critical for managing potential environmental and anthropogenic impacts in drylands. However, modeling wind erosion on partially vegetated surfaces is a complex problem that has remained challenging for researchers. We present the new, coupled cellular automaton Vegetation and Sediment TrAnsport (ViSTA) model, which is designed to address fundamental questions about the development of arid and semiarid landscapes in a spatially explicit way. The technical aspects of the ViSTA model are described, including a new method for directly imposing oblique wind and transport directions onto a cell‐based domain. Verification tests for the model are reported, including stable state solutions, the impact of drought and fire stress, wake flow dynamics, temporal scaling issues, and the impact of feedbacks between sediment movement and vegetation growth on landscape morphology. The model is then used to simulate an equilibrium nebkha dune field, and the resultant bed forms are shown to have very similar size and spacing characteristics to nebkhas observed in the Skeleton Coast, Namibia. The ViSTA model is a versatile geomorphological tool that could be used to predict threshold‐related transitions in a range of dryland ecogeomorphic systems. Key Points: A new coupled vegetation/sediment transport (ViSTA) model for dryland environments is presented The technical aspects of the ViSTA model are described, verification tests for the model are reported, and a nebkha dune field is simulated The model is a versatile geomorphological tool that could ultimately be used to predict transitions in many dryland ecogeomorphic systems